Decreased Vitamin B12 Levels in Children with Nocturnal Enuresis. (26th January 2012) - Altunoluk, Bülent; Davutoglu, Mehmet; Garipardic, Mesut; Bakan, Vedat
Abstract : Objectives . Nocturnal enuresis is a common pediatric problem, the etiology of which is unclear. In the present study, vitamin B12 and folate levels were measured in children with nocturnal enuresis and compared with those in healthy control group children to investigate whether there was any relation with enuresis and neurogenic maturation as a first time in the literature. Methods . In this cross-sectional study, we included thirty children (16 girls, 14 boys) who had presented with primary nocturnal enuresis (PNE) complaints in the study group and 31 children (13 girls, 18 boys) in the control group. Body weight and height measurements were obtained and complete blood counts and vitamin B12 and folate levels were measured in all children. Results . No difference was found in age, height, and weight between study and control groups. Also the mean levels of the hemoglobin, hematocrit, and mean corpuscular volume (MCV) were not different between the two groups. Significantly lower mean vitamin B12 and folate levels were found in the enuresis group compared with the control group. Conclusions . Further studies are needed to clarify B12 and folate deficiency in larger series so that these tests can be included in routine investigations of enuretic children.